Reductive decyanation of α-cyano and α-alkoxycarbonyl substituted nitriles promoted by samarium(II) iodide - KANG, HY; HONG, WS; CHO, YS; KOH, HY (Elsevier BV, 1995)
Decyanation of geminal dinitriles and alpha-alkoxycarbonyl substituted nitriles promoted by samarium(II) iodide has been efficiently achieved. This method has advantages over the previously known radical route using tin hydride with respect to applicable substrates and the reaction temperature employed. This decyanation could broaden the synthetic applicability of the nitrile derivatives.